2013
DOI: 10.1016/s0924-9338(13)76555-6
|View full text |Cite
|
Sign up to set email alerts
|

1545 – Inmates trauma and dissociation

Abstract: Trauma and dissociation have been shown to be prevalent among inmate population. However, despite the high rate of traumatic experiences in this population, few studies have aimed on potential links between traumatic experiences and dissociation, specially considering the types of crime. This study sought to examine the severity of dissociative and traumatic experiences, as well as relationships between types of crime, types of trauma, and dissociation.Twenty-nine inmates (mean age = 37.8 ± 10.0) were examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The present study aimed to address most of the controversial issues mentioned above. First, in line with previous findings (Espirito-Santo & Costa, 2013;Mitchell, 2006;Moskowitz et al, 2005;Ruiz et al, 2008;Snow & Beckman, 1996), we expected that inmates reported higher degrees of dissociative experiences than controls. Then, we sought to corroborate evidence of the relationships between dissociative and other psychiatric symptoms.…”
Section: Introductionsupporting
confidence: 79%
See 3 more Smart Citations
“…The present study aimed to address most of the controversial issues mentioned above. First, in line with previous findings (Espirito-Santo & Costa, 2013;Mitchell, 2006;Moskowitz et al, 2005;Ruiz et al, 2008;Snow & Beckman, 1996), we expected that inmates reported higher degrees of dissociative experiences than controls. Then, we sought to corroborate evidence of the relationships between dissociative and other psychiatric symptoms.…”
Section: Introductionsupporting
confidence: 79%
“…Taking a closer look at the dissociation literature, one could conclude that there is a disproportion of samples recruited, with a landslide majority of studies involving clinical, community, and student samples (e.g., Evren et al, 2013;Foote, Smolin, Kaplan, Legatt, & Lipschitz, 2006;Gutiérrez Wang, Cosden, & Bernal, 2011;Maaranen, 2008;Maaranen et al, 2005;Van IJzendoorn, 1996;Vogel, Spitzer, Barnow, Freyberger, & Grabe, 2006;Xiao et al, 2006;Yoshizumi, Murase, Murakami, & Takai, 2007), and only a handful of them addressing dissociation in offender samples (Ciulla & Caretti, 2012;Dietrich, 2003;Lancaster, Compton, White, Bowers, & Herring, 1998;Lewis, Yeager, Swica, Pincus, & Lewis, 1997;Mitchell, 2006;Ruiz, Poythress, Lilienfeld, & Douglas, 2008;Walker, 2002). Although inmates often present with higher rates of dissociative symptoms Dietrich, 2003;Espirito-Santo & Costa, 2013;McLeod, Byrne, & Aitken, 2004;Snow & Beckman, 1996), and dissociation itself has been reported as a risk factor for antisocial and violent behavior in offender populations (Dietrich, 2003;Moskowitz, 2004;Poythress, Skeem, & Lilienfeld, 2006), there is a lack of studies exploring the associations of dissociation with external correlates in these populations. Some of them (e.g., Ruiz et al, 2008;Spitzer et al, 2001) supported the relationship of dissociation with antisocial behavior and aggression, as well as with early traumatic experiences.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations